Online grocery purchasing in Mississippi: associations with broadband, rurality, and household characteristics - Will Davis; Jordan W. Jones; Elizabeth Canales; Ayoung Kim; David R. Buys (Frontiers in Nutrition)
IntroductionThis study investigates the sociodemographic, economic, and area characteristics associated with Online Grocery Purchasing (OGP) use among adult residents of Mississippi. Understanding these factors is important in a largely rural and low-income state to address barriers and enhance accessibility.MethodsData were collected from a 2022 online pilot survey (n = 398) and secondary sources. A logistic regression model was used to analyze associations between self-reported OGP use and factors including local broadband quality, sociodemographic and economic characteristics, the local food environment, and participation in government nutrition assistance programs.ResultsThe analysis revealed that higher education and income levels are positively associated with the likelihood of OGP use. Conversely, age and rural residence emerged as potential barriers. Although broadband disparities are widespread across Mississippi, self-reported home internet type and local internet speeds showed inconsistent associations with OGP participation across analyses.DiscussionThe findings underscore the nuanced interplay of accessibility and individual-level contexts in shaping OGP behavior. This study highlights the importance of addressing both structural and individual-level barriers to improve access to online grocery services in rural and low-income areas.